DOES THE CHOICE OF ALTERNATIVE ENERGY SOURCES OF HOUSEHOLDS AFFECT COST OF COOKING IN RURAL AREAS OF PESHAWAR - Mahfooz Khan; Dr. Samiuddin Shaikh; Dr. Aisha Bashir Shah; Paras Hasnain Channar; Taimoor Jan; Mohammad Sohail Khan (International Journal of Contemporary Issues in Social Sciences, 2023)
This study is based on does the choice of alternative energy sources effect cost of cooking in rural areas of Peshawar. The main objective of the study was to investigate the effect of the choice of alternative energy sources on cost of cooking in the study area. Multi-stage sampling technique was used for data collection. In the first stage, three rural union councils were purposively selected. In the second stage, three villages each from three union councils were selected. In the third stage, the households were selected for data collection regarding the choice of alternative energy sources for cooking in the study area. A sample of 5 percent out of total households which were 512 sample households was chosen randomly. In this study multiple linear regression model and robust regression were also used for the cost incurred on different energy sources. The result of multiple linear regression model indicated that the effect of family size, distance from home to the nearest market, education level and income of the sample households have significant at 0.05 level and positive effect on the cost of energy sources for cooking in the study area. The study concluded that family size has a negative relationship with the use of electricity and firewood while the income of household head, education level of the household head has a positive relationship with the use of electricity, natural gas and firewood for cooking purpose in the study area. The study also concluded that the use of natural gas was less costly as compared to other alternative energy sources like electricity and firewood. The study recommends that government should make out all efforts to ensure the availability of natural gas for the use of cooking purpose in the study area. The government should offer alternative sources, like solar energy for cooking and provide them modern and cheap energy sources.